The emergence of Halocladius variabilis (Staeger) (Diptera: Chironomidae) in the surroundings of the Tvärminne Biological Station in the northern Baltic Sea - Hirvenoja, Mauri; Palmén, Ernst; Hirvenoja, Elina (Entomologica Fennica, 2006)
The emergence of the marine species Halocladius variabilis (Staeger) in the surroundings of theTvärminne Biological Station (about 6‰S) in the northernBaltic Sea in 1952–1953 is outlined. Most individuals emerged in the submerged funnel traps used in the study from the last half of May to the end of June. The population density in the sites studied varied between 0 and 328 indiv./m2; wide areas had a population density of nearly 10 indiv./m2. No emergence was found in the traps nearest to the buildings of the station, but the highest numbers of the emergence occurred in the most distant sites studied.